2009
DOI: 10.1186/1475-2875-8-66
|View full text |Cite
|
Sign up to set email alerts
|

Malaria misdiagnosis in Uganda – implications for policy change

Abstract: Background: In Uganda, like in many other countries traditionally viewed as harbouring very high malaria transmission, the norm has been to recommend that febrile episodes are diagnosed as malaria. In this study, the policy implications of such recommendations are revisited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
125
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(138 citation statements)
references
References 25 publications
11
125
1
Order By: Relevance
“…Finally, we only interviewed laboratory and medical staff at a single referral hospital in Malawi, but respondents identified challenges that have been identified in other lowresource laboratory settings. 1,[3][4][5][6]12 The results of this work provide evidence and context for challenges in the laboratory diagnostic process, motivating the development of interventions to improve the laboratory workflow and stature within the hospital. The choice to capture the pre-and post-analytical phases by including providers from the medical ward and laboratory staff, recognizes that challenges at any point in the process, regardless of location, undermine the ability of laboratory testing to improve health-care delivery and health outcomes.…”
Section: Interview 13 (Medical Staff)mentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we only interviewed laboratory and medical staff at a single referral hospital in Malawi, but respondents identified challenges that have been identified in other lowresource laboratory settings. 1,[3][4][5][6]12 The results of this work provide evidence and context for challenges in the laboratory diagnostic process, motivating the development of interventions to improve the laboratory workflow and stature within the hospital. The choice to capture the pre-and post-analytical phases by including providers from the medical ward and laboratory staff, recognizes that challenges at any point in the process, regardless of location, undermine the ability of laboratory testing to improve health-care delivery and health outcomes.…”
Section: Interview 13 (Medical Staff)mentioning
confidence: 99%
“…A study of almost 200 health facilities in Uganda found that roughly 25% had a functioning microscope, but in those facilities, only 35% of malaria diagnoses used a malaria slide examination. 3 In Tanzania, a study of 4,670 patients diagnosed with severe malaria found that fewer than 50% had a blood smear result consistent with the disease. 6 This can result in worsened health status for patients inappropriately treated with antimalarials for a condition such as bacterial sepsis, which has a similar presentation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid Diagnostic Tests (RDTs) are being promoted as a solution to these diagnostic challenges in settings with no or poor quality microscopy. Malaria RDTs have been found to be accurate under controlled conditions, easy to use and interpret and can be performed with basic training and equipment (Nankabirwa et al, 2009;Zikusooka et al, 2008). Several studies have also suggested RDTs can be cost-effective when compared with no testing or microscopy although this depends on the prevalence of malaria, costs of testing and treatment and critically whether the treatment prescribed is consistent with the outcome of the malaria test (Lubell et al, 2008;Shillcutt et al, 2008;Zikusooka et al, 2008;Zurovac et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…5,6 A consequence of the prolonged neglect of laboratories in malaria case management is that, even when quality laboratory services are available, clinicians too frequently ignore negative results. [7][8][9][10][11][12] The reduction in clinical malaria in several countries [13][14][15][16] and the use of expensive artemisinin-based combination therapeutic (ACT) antimalarial drugs call for case management practices that emphasize parasitologic confirmation, because continued use of ACTs in non-malaria cases represents a waste of resources and eventually, is unsustainable. Indiscriminate use of ACTs could create sufficient drug pressure that hastens development of resistant parasites, a situation that has begun to develop in Southeast Asia.…”
Section: Introductionmentioning
confidence: 99%